Postmigracyjny background i co z niego wynika. Rewolty tożsamościowe dzieci późnych przesiedleńców w prozie faktograficznej Emilii Smechowski, "My, super imigranci" - Szydłowska, Joanna (Załącznik Kulturoznawczy, 2023)
The Post-migrant Background and What it Entails: Identity Shifts in the Children of Late Repatriates in the Factual Prose of Emilia Smechowski, My, super imigranci The article analyzes an extensive nonfiction book by Emilia Smechowski, a Polish-born author who relocated to Germany as a child. The purpose of the examination is to determine how the migrant and post-migrant experience influenced the author and her characters. The paper looks at the consequences of the tensions resulting from the migrant background as regards genre choices (reportage/self-reportage/autobiography), thematic interests (the text grew between cultures and languages), and identity definitions. The book is approached as an identity and emancipation project of the speaking subject. It is an account of coping with difficult post-migrant experiences on a micro- and macro-scale (a Polish intelligentsia family vs. German public discourse).